Measured overall heat transfer coefficient of a suspended particle device switchable glazing. (1st December 2015) - Ghosh, Aritra; Norton, Brian; Duffy, Aidan
Highlights: Test cell experimental characterisation is performed for a suspended particle device (SPD) switchable glazing. The overall heat transfer coefficient of an SPD glazing has been calculated and compared with double-glazing. Thermal behaviour of SPD glazing was improved by adding one double-glazing. Abstract: Suspended particle device (SPD) switchable glazing can change optical transmission from "opaque" state to "transparent" state in the presence of an alternating current (AC) power supply. It can be applied to control internal temperatures in buildings. Thermal characterisation of both SPD and same area of a double-glazing sample was accomplished using an outdoor test cell in Dublin, Ireland. The overall heat transfer coefficients ( U value) were calculated for both systems from the experimental data. The average U values for SPD and double glazing samples were found to be 5.9 W/m 2 K and 2.98 W/m 2 K, respectively. Addition of double-glazing to this SPD switchable single glazing offered a U value of 1.99 W/m 2 K.